(untitled) (Research, Society and Development, 2022)
Objective: To analyze data regarding the profile of hospitalizations for mental and behavioral disorders in the state of Piauí, before and during the COVID-19 pandemic. Methodology: This is a quantitative and descriptive epidemiological study. Its base is based on secondary data from hospitalization records of individuals with Mental and Behavioral Disorders extracted from the Department of Informatics of the Brazilian Unified Health System (DATASUS). Results: Variations in the number of hospitalizations for mental and behavioral disorders were evaluated and compared from August 2017 to December 2019 and from January 2020 to August 2022 by health region, gender, race/ color and age group. Final considerations: In relation to hospital admissions for Mental and Behavioral Disorders from August 2017 to August 2022, a slight decrease in hospital admissions was noted, which the preventive measures adopted to contain the coronavirus, such as lockdown and social isolation, can have limited hospital admissions; in addition to the time frame adopted in the research, it does not include the years 2017 and 2022 in their entirety, due to data availability.